Effect of Cucurbita pepo (pumpkin) seed extracts on serum prolactin levels of non-lactating female Wistar rats - Anyanwu, C. F.; Georgewill, U. O.; Chioma, G. C. (Journal of Medicinal Herbs and Ethnomedicine, 2024)
Despite the traditional use of Cucurbita pepo seed to enhance milk production during lactation, its effect in non-lactating females remains scarce. The aim of this study was to investigate the effect of n-hexane (nHE), Dichloromethane (DCM) and Aqueous ethanol (Aq. Eth) extracts of C. pepo seed on serum prolactin levels of non-lactating female Wistar rats. A total of 44 non pregnant female rats weighing 190 g were randomly grouped into 11 groups of 4 rats, for treatment as follows: A (control): 0.5 mL 5% Tween 80 (vehicle); B (positive control): 10mg/kg Clomiphene Citrate, C, D & E: 142.86, 285.71, and 428.57 mg/kg of nHE; F, G & H: 142.86, 285.71, and 428.57 mg/kg of DCM; and I, J & K: 142.86, 285.71, and 428.57 mg/kg of Aq. Eth extracts of C. pepo seed. Vaginal cytology monitored the estrous cycle daily, and blood samples were obtained for serum prolactin at various oestrus cycle phases. There was no significant (P>0.05) variation in serum prolactin levels in rats treated with 142.86 mg/kg, 285.71 mg/kg, and 428.57 mg/kg of all three extracts of C. pepo during the Proestrus, estrus, and metestrus phases relative to the control. A significant (P<0.05) increase in serum prolactin levels was observed at the diestrus phase in rats treated with 142.86 mg/kg, 285.71 mg/kg, and 428.57 mg/kg of n-HE, 428.57 mg/kg of DCM and 142.86 mg/kg, 285.71 mg/kg of Aq. Eth extracts of C. pepo seed, relative to the positive control group. Rats treated with 142.86 mg/kg of Aq. Eth had a significant increase in serum prolactin in the diestrus phase, relative to the control. The findings of this study show that C. pepo seed extracts may exhibit a phase-specific effect within the estrous cycle of non-lactating female rats and as such may have potential applications in regulating prolactin levels.